High resolution melting analysis (HRM) as a new tool for the identification of species belonging to the Lactobacillus casei group and comparison with species-specific PCRs and multiplex PCR. (April 2015) - Iacumin, Lucilla; Ginaldi, Federica; Manzano, Marisa; Anastasi, Veronica; Reale, Anna; Zotta, Teresa; Rossi, Franca; Coppola, Raffaele; Comi, Giuseppe
Abstract: The correct identification and characterisation of bacteria is essential for several reasons: the classification of lactic acid bacteria (LAB) has changed significantly over the years, and it is important to distinguish and define them correctly, according to the current nomenclature, avoiding problems in the interpretation of literature, as well as mislabelling when probiotic are used in food products. In this study, species-specific PCR and HRM (high-resolution melting) analysis were developed to identify strains belonging to the Lactobacillus casei group and to classify them into L. casei, Lactobacillus paracasei and Lactobacillus rhamnosus . HRM analysis confirmed to be a potent, simple, fast and economic tool for microbial identification. In particular, 201 strains, collected from International collections and attributed to the L. casei group, were examined using these techniques and the results were compared with consolidated molecular methods, already published. Seven of the tested strains don't belong to the L. casei group. Among the remaining 194 strains, 6 showed inconsistent results, leaving identification undetermined. All the applied techniques were congruent for the identification of the vast majority of the tested strains (188). Notably, for 46 of the strains, the identification differed from the previous attribution. Highlights: Species-specific PCRs and HRM analysis yielded accurate results. 194 out of the 201 tested strains resulted to belong to the L. casei group. For six strains out of 194 the identification methods were in disagreement. The identity of these 6 strains remains unclear. Identification of 46 was in disagreement with the original one.